Pesquisa e desenvolvimento no setor de sementes de arroz irrigado no Rio Grande do Sul - Marquesan, Fábio Freitas Schilling (2008)
The aim of this work was to investigate the ways in which the organizations dedicated to the research and development (R&D) of rice irrigated seeds in the Rio Grande do Sul State face the action of opportunist agents, which promote the commerce and the informal use of genetic materials protected by Law. The research problem was structured as the following questions: How do the agents involved in the R&D of rice irrigated seeds in RS face the difficulties of remuneration in the investments carried out during the development of new varieties of seeds; and how do these difficulties intervene in the management of competitive strategies? For answering this question, the vision of the responsible right-handers for the programs management in R&D, from five organizations that act in the sector, was investigated. The Theoretical Reference used in this research was based on the theories of Industrial Organization (IO), New Institutional Economy (NIE), Institutional Environment (IE) and Transactions Cost Economics (TCE). The research is an exploratory case study of applied nature, whose way of approach and data analysis is qualitative, of the type content analysis. The research also presents characteristics of a census, since there are five units that follow the study requirements and all of them have offered answers to the research questionnaire. The primary data collection was done through a transversal cut survey, carried out from March to July, 2008. The results have shown that, among the consulted organizations, only one did not have its seeds illegally used. However, all of them pointed out they have been affected by acts involving the inappropriate use of legally protected seeds. The five organizations have affirmed that the prescription gotten by the commerce of rice seeds in the RS State, up to the moment, is not enough to finance its activities of R&D. As consequence, there was a retraction in the number of launchings of rice seeds through the varieties. The strategies already adopted for the continuity of the investments are analyzed, necessarily, by the R&D of anti-reproductive attributes of the proper seeds. Thus, the majority of the resources were directed for the development of rice hybrids as the main strategy of the copyright protection. Some discredit from the sector in relation to the coordination role of the seeds production system and commercialization in the RS State was observed. In the consulted professionals view, it would be essential that more intensive institutional actions were undertaken in both inspection and in the control of such process. For them, the application of severe criminal punishment to the offenders would be an efficient way to promote the fulfillment of the Laws and, thus, trying to improve the coordination in the sector. It was also observed the awareness campaigns should be more stimulated in order that all the involved ones in the question could recognize the importance of royalties payment (or another way of investments remuneration) as a way to guarantee the maintenance of the R&D sector of the irrigated rice seeds in the RS State.